PHENOMENON OF CHILDFREE CAMPAIGN HADITH PERSPECTIVE: HADITH ANALYSIS MULTIPLIES CHILDREN USING YUSUF QARDHAWI’S HERMENEUTICS - Nasrulloh Nasrulloh; Abdullah Amjad; Al-Fairu Zabadi; Achmad Bagus Syaifullah; Ahmad Abi Najih; Shihab Irfani (International Conference on Social and Islamic Studies, 2021)
Childfree is an understanding that believes that a family does not need to have children orchildren, Childfree is a lifestyle of refusing to give birth, adopt, or in other words do notwant to have children for married couples. Childfree is commonly done by many people,whether female or male, either the choice is forced or with their own awareness. Thephenomenon of childfree raises pros and cons among young women, they use certainpropositions to strengthen their arguments. Therefore, this paper discusses thephenomenon of childfree perspective of hadith, especially hadith about multiplyingoffspring that are interpreted from yusuf al-Qardhawy's hermeneutic perspective. Thisarticle falls into the category of qualitative research with reaserch library types that aredata-based libraries, reading, recording and managing research materials. The analyticalmethod used in this study is descriptive analysis with a partial-simultaneous approach inthe realm of hadith. The results showed that the phenomenon of childfree is contrary tothe hadith of multiplying offspring, because in it there is an invitation not to havechildren, while the Prophet (peace be upon him) ordered his people to marry fertilewomen in order to have children. Women are equipped with great excess affection inorder to educate their children to create a superior and beautiful generation. Apart fromthe pros and cons of childfree writers, children are allowed to themselves and are notallowed to campaign to the public.